Mark of Cain(ada): Racialized Security Discourse in Canada's National Newspapers. - Smolash, Wendy Naava (University of Toronto Quarterly)
This essay compares coverage in two of Canada's national newspapers, the "Globe and Mail" and the "National Post," of two high-profile anti-terrorism cases: Project Thread (2003) and the Toronto 18 (2006). I read these media stories as narratives, open to literary analysis, that allow us to pry open and critique Canada's dominant national security discourse. These national newspaper narratives, I argue, mobilize racialized signs of otherness that legitimate and naturalize national security discourses, even when accusations are withdrawn by officials. This raises urgent questions about the ways in which media may naturalize state violence against Muslim, Arab, and South Asian citizens and non-citizens within Canada's borders.